Analysis of Board of Directors Gender Diversity in the Impact of Corporate Governance on Earnings Management - Novrica, Farin; Tarmidi, Deden; Herliansyah, Yudhi (Research Horizon, 2024)
This study aims to analyze the effect of Board Gender Diversity in Corporate Governance on earnings management in technology companies. The sample of this study included 36 technology companies listed on the Indonesia Stock Exchange (IDX) during the period 2012-2022. The analysis technique used is multiple regression analysis and t-test by STATA program. The independent variables in this study include institutional ownership, managerial ownership, and audit committee, while the dependent variable is earnings management. The results showed that in simultaneous testing (F test), the variables of institutional ownership, managerial ownership, and audit committee significantly affect earnings management. Meanwhile, in partial testing (T test), there is no difference in the effect of institutional ownership and audit committee on earnings management in companies led by male directors and female directors. However, there is a significant difference in the effect of managerial ownership on earnings management between companies led by male directors and companies led by female directors.